Lectio divina: the medieval experience of reading - Robertson, Duncan (Cistercian studies series, 2011)
During the Middle Ages the act of reading was experienced intensively in the monastic exercise of lectio divina--the prayerful scrutiny of passages of Scripture, "savored" in meditation, memorized, recited, and rediscovered in the reader's own religious life. The rich literary tradition that arose from this culture includes theoretical writings from the Conferences of John Cassian (fifth century) through the twelfth-century treatises of Hugh of St. Victor and the Carthusian Guigo II; it also includes compilations, literary meditations, and scriptural commentary, notably on the Song of Songs. This study brings medievalist research together with modern theoretical reflections on the act of reading in a consolidation of historical scholarship, spirituality, and literary criticism. --Publisher description